Perubahan Tinggi Sel Epitelium Villi Ventrikulus Marmut (Cavia porcellus L.) Setelah Pemberian Teh Hijau - Muliani, Hirawati; Kasiyati, Kasiyati (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
The research of the of Guniea Pig Ventriculus Villi Epithelium Cell Height After Was Given With Green Tea is aimed to know the effect of green tea on ventriculus villi epithelium cell height of female guinea pig. Twenty four female guinea pig were acclimated during 1 week and then alloted into 4 group, each group was treated as follows : P0 : treated with boiled water (= control); P1 : treated with 3 gram green tea / 200 cc water ; P2 : treated with 5 gram green tea / 200 cc water; P3 : treated with 7 gram green tea / 200 cc water. Green tea water were given by spuit without needle to the mouth of guinea pig. Amount of green tea water was 20 ml / test animal/ day. Long of the treatment was 2 months. Replication was 6 times. Main parameter observed was the change of ventriculus villi epithelium cell height. Supporting parameter was guinea pig body weight after treatment, room temperature, and room humidity. Quantitative data was analyzed by varians analysis with Completely Random Design. The result was given of green tea has no effect to the height of guinea pig ventriculus villi epithelium cell height, but metaplasia occurs, there is anyÂ epithelium columner cells of the villi turn into epithelium squamous cell, and green tea decreases guinea pig body weight after treatment,